Adipose Tissue Is a Neglected Viral Reservoir and an Inflammatory Site during Chronic HIV and SIV Infection - Damouche, Abderaouf (PLoS Pathog, 2015)
Two of the crucial aspects of human immunodeficiency virus (HIV) infection are (i) viral persistence in reservoirs (precluding viral eradication) and (ii) chronic inflammation (directly associated with all-cause morbidities in antiretroviral therapy (ART)-controlled HIV-infected patients). The objective of the present study was to assess the potential involvement of adipose tissue in these two aspects. Adipose tissue is composed of adipocytes and the stromal vascular fraction (SVF); the latter comprises immune cells such as CD4(+) T cells and macrophages (both of which are important target cells for HIV). The inflammatory potential of adipose tissue has been extensively described in the context of obesity. During HIV infection, the inflammatory profile of adipose tissue has been revealed by the occurrence of lipodystrophies (primarily related to ART). Data on the impact of HIV on the SVF (especially in individuals not receiving ART) are scarce. We first analyzed the impact of simian immunodeficiency virus (SIV) infection on abdominal subcutaneous and visceral adipose tissues in SIVmac251 infected macaques and found that both adipocytes and adipose tissue immune cells were affected. The adipocyte density was elevated, and adipose tissue immune cells presented enhanced immune activation and/or inflammatory profiles. We detected cell-associated SIV DNA and RNA in the SVF and in sorted CD4(+) T cells and macrophages from adipose tissue. We demonstrated that SVF cells (including CD4(+) T cells) are infected in ART-controlled HIV-infected patients. Importantly, the production of HIV RNA was detected by in situ hybridization, and after the in vitro reactivation of sorted CD4(+) T cells from adipose tissue. We thus identified adipose tissue as a crucial cofactor in both viral persistence and chronic immune activation/inflammation during HIV infection. These observations open up new therapeutic strategies for limiting the size of the viral reservoir and decreasing low-grade chronic inflammation via the modulation of adipose tissue-related pathways.